2009
DOI: 10.1016/j.biomaterials.2009.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Poly(glycerol-dodecanoate), a biodegradable polyester for medical devices and tissue engineering scaffolds

Abstract: In this paper we describe the mechanical and biological features of a thermosetting polyester synthesized from glycerol and dodecanedioic acid named Poly-Glycerol-Dodecanoate (PGD). This polymer shows a glass transition temperature (Tg) around 32°C, and this accounts for its mechanical properties. At room temperature (21°) PGD behaves like a stiff elastic-plastic material, while at body temperature (37°C), it shows a compliant non-linear elastic behavior. Together with biodegradability and biocompatibility PGD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 11 publications
4
85
0
Order By: Relevance
“…Similar to PGS, we have successfully developed poly(glycerol-dodecanoate) (PGD) by thermal condensation of glycerol and dodecanedioic acid and demonstrated its unique shape memory property 1 . Unlike stiffer synthetic materials poly(hydroxyl butyrate) or poly(L-lactide) (Young's moduli of 250 MPa and 660 MPa, respectively), PGD exhibits elastomeric property like rubber, with a Young's modulus of 1.08 MPa when the temperature is above 37 °C, which is a close match to the in-situ peripheral nerve (0.45 MPa).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to PGS, we have successfully developed poly(glycerol-dodecanoate) (PGD) by thermal condensation of glycerol and dodecanedioic acid and demonstrated its unique shape memory property 1 . Unlike stiffer synthetic materials poly(hydroxyl butyrate) or poly(L-lactide) (Young's moduli of 250 MPa and 660 MPa, respectively), PGD exhibits elastomeric property like rubber, with a Young's modulus of 1.08 MPa when the temperature is above 37 °C, which is a close match to the in-situ peripheral nerve (0.45 MPa).…”
Section: Introductionmentioning
confidence: 99%
“…HAFs were viable throughout the course of the study, with similar trends on PGD and polystyrene [19].…”
Section: Neural Tissue Engineeringmentioning
confidence: 76%
“…Cytotoxicity of PGD was therefore expected to be minimal, as these monomers are compatible with biological systems. In order to explore this hypothesis, human aortic fibroblasts (HAFs) were seeded on PGD-coated glass slides and polystyrene plates [19]. The cell density on the polystyrene plates was higher than that of cells on PGD-coated slides for approximately 18 days.…”
Section: Neural Tissue Engineeringmentioning
confidence: 99%
“…Synthesis of the PGD polymer was by mixing of glycerol and DDA in 1:1 molar ratio and heating at 120°C for 4~5 days. Cell growth studies revealed that PGD-treated plates initially show slower human fibroblast cell growth compared to controls, but at approximately day 18 cell growth in these plates had reached the same level as for control cell culture plates (71). It seems that this polymer is a good candidate for use in drug delivery thanks to its good biodegradability (mainly through surface erosion), biocompatibility, solubility in polar solvents (e.g.…”
Section: Novel Polymeric Nps Poly(glycerol-dodecanoate) (Pgd)mentioning
confidence: 99%
“…Migneco and Huang reported the synthesis of a novel polyester from glycerol and dodecanedioic (DDA) for biomedical applications, which maintains good mechanical and biological properties during degradation (71). This novel polyester poly(glyceroldodecanoate) (PGD) was formed mainly through ester bonds and its degradation is through the hydrolysis mechanism.…”
Section: Novel Polymeric Nps Poly(glycerol-dodecanoate) (Pgd)mentioning
confidence: 99%